Analisis Kritis Model CGE Seung Rae Kim : Ketidakpastian Preferensi Politis, dan Stabilisasi : Kontrol Stochastic Yang Mempergunakan Model-Model CGE Dinamis - Martha Hendrati, Ignatia (Jurnal Riset Ekonomi & Bisnis, 2007)
Models of Computable General Equilibrium ( traditional CGE) disregard uncertainty even when wearied area like compilation of environmental model which full of uncertainty of economics. As comparison, most theory models control focused at uncertainty effects. Merger of tradition compilation model of CGE and control can yield modelsÂ  with dynamics of eksplisit careful treatment and uncertainty. This handing out is continuation step to optimal control model merger with models of CGE dynamic. This handing out show techniques benefit of CGE in theory application control and specify practical guidance line to policy maker in the field of newly. Besides this handing out also study relation between economic stabilization and fiscal policy device optimal environment in dynamic public balance framework of stochastic. Uncertainty, process adjustment of amount short term andÂ  preferensi political ( for example, excessive stabilization priority in industry ) allowed for to investigate what time directive adjustment of optimal economics to be governmental with target of policy eksplisit. Optimal Control solution can differ not only effect of differences in just elementary model structure or assumption, but also depend on uncertainty about level of parameters in economics. Is peculiarly indicated that economic stabilization performance can differ signifikan with preference / uncertainty of unsymmetrical politics in all sector of industrial. In such case, restructuring of components in compilation of economic model common CGE can identify policies in the world of having the character of stochastic which possible apply approach of compilation of theory model- control ( traditional macroeconomics) Keywords: Optimal Control, Models Of CGE Dynamic, Uncertainty, Process Adjustment, Political Preference, Macroeconomics Stabilization